2014
DOI: 10.4292/wjgpt.v5.i3.113
|View full text |Cite
|
Sign up to set email alerts
|

Use of methotrexate in inflammatory bowel disease in 2014: A User’s Guide

Abstract: Methotrexate has been used an immunomodulator in many autoimmune diseases, including inflammatory bowel disease. However, many physicians are unfamiliar or uncomfortable with its use in the management of inflammatory bowel disease. We summarize the data for use of methotrexate in common clinical scenarios: (1) steroid dependant Crohn's disease (CD); (2) maintenance of remission in steroid free CD; (3) azathioprine failures in CD; (4) in combination therapy with Anti-TNF agents in CD; (5) decreasing antibody fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…However, methotrexate can be used as an effective immune-modulator in inflammatory bowel disease. 70 Of importance to dentists, methotrexate can commonly cause ulcerative stomatitis 71 and recent case reports have identified Epstein-Barr associated lympho-proliferative disorders occurring in the gingiva of patients taking methotroxate, causing gingival ulceration. 72,73 Biologic anti-TNF agents Both infliximab and adalimumab are relatively new antibody-based drugs against TNF (tumour necrosis factor), which is a cytokine agent in the body's immune response, upregulated in inflammatory conditions such as IBD.…”
Section: Methotrexatementioning
confidence: 99%
“…However, methotrexate can be used as an effective immune-modulator in inflammatory bowel disease. 70 Of importance to dentists, methotrexate can commonly cause ulcerative stomatitis 71 and recent case reports have identified Epstein-Barr associated lympho-proliferative disorders occurring in the gingiva of patients taking methotroxate, causing gingival ulceration. 72,73 Biologic anti-TNF agents Both infliximab and adalimumab are relatively new antibody-based drugs against TNF (tumour necrosis factor), which is a cytokine agent in the body's immune response, upregulated in inflammatory conditions such as IBD.…”
Section: Methotrexatementioning
confidence: 99%
“…It is used predominantly for immunosuppression in autoimmune diseases and as chemotherapy. In CD it has to date remained in treatment algorithms as a salvage therapy for patients who have failed to respond or became intolerant to azathioprine [97] . However, its use is not so common in the clinical routine for CD but MTX seems to be sufficient in maintenance therapy.…”
Section: CDmentioning
confidence: 99%
“…Recently a user's guide was published which favors the safe and efficient use of MTX in several clinical conditions of CD and UC. The authors Swaminath et al [97] provided an ease to use algorithm. MTX is largely used as a second line therapy after AZA failure.…”
Section: CDmentioning
confidence: 99%
“…However, MTX may be considered if no contraindications are present [38] . A new study by Haisma et al [39] studied the effectiveness of MTX for maintaining remission in 113 pediatric CD patients with prior failure or intolerance to TPs.…”
Section: Use In CDmentioning
confidence: 99%
“…Similarly, the recent Toronto Consensus guidelines strongly recommend against the use of MTX monotherapy for induction or maintenance of remission in UC. Two ongoing large randomized controlled trials (METEOR and MERIT-UC) are assessing the efficacy of parenteral MTX 25 mg weekly in the induction and maintenance of remission in steroid-dependent or refractory UC [38] . Preliminary results of the METEOR study on 111 patients showed improved clinical remission without steroids (42% MTX vs. 23.5% placebo, p = 0.04) but no significant effect on the primary composite end point at week 16 (32% MTX vs. 20% placebo, p = 0.15) or on mucosal healing (35% MTX vs. 25.5% placebo, p = NS) [48,49] .…”
Section: Use In CDmentioning
confidence: 99%